Melt Electrospinning of Nanofibers from Medical‐Grade Poly(ε‐Caprolactone) with a Modified Nozzle. Issue 44 (13th October 2020) - Großhaus, Chiara; Bakirci, Ezgi; Berthel, Marius; Hrynevich, Andrei; Kade, Juliane C.; Hochleitner, Gernot; Groll, Jürgen; Dalton, Paul D
Abstract: Melt electrospun fibers, in general, have larger diameters than normally achieved with solution electrospinning. This study uses a modified nozzle to direct‐write melt electrospun medical‐grade poly(ε‐caprolactone) onto a collector resulting in fibers with the smallest average diameter being 275 ± 86 nm under certain processing conditions. Within a flat‐tipped nozzle is a small acupuncture needle positioned so that reduces the flow rate to ≈0.1 µL h −1 and has the sharp tip protruding beyond the nozzle, into the Taylor cone. The investigations indicate that 1‐mm needle protrusion coupled with a heating temperature of 120 °C produce the most consistent, small diameter nanofibers. Using different protrusion distances for the acupuncture needle results in an unstable jet that deposited poor quality fibers that, in turn, affects the next adjacent path. The material quality is notably affected by the direct‐writing speed, which became unstable above 10 mm min −1 . Coupled with a dual head printer, first melt electrospinning, then melt electrowriting could be performed in a single, automated process for the first time. Overall, the approach used here resulted in some of the smallest melt electrospun fibers reported to date and the smallest diameter fibers from a medical‐grade degradable polymer using a melt processing technology. Abstract : Melt electrospinning traditionally produces larger diameter fibers than solution electrospinning, however this study incorporates an acupuncture needle within a nozzle to both reduce the flow and increase the charge within the Taylor cone. The result is melt electrospun nanofibers from medical‐grade poly(ɛ‐caprolactone), beneficial in biomedical applications where solvent accumulation and toxicity are a concern.